OPEN MESH PREPERITONEAL GROIN HERNIA REPAIR - Ade Ansari, Witia; Handayani, Sri Putri; Febriana, Dita; Utami, Deviani; Wirawan, Ahmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Surgeons are currently debating the best method for inguinal hernia repair, with a focus on minimizing recurrences and addressing chronic pain. Laparoscopic approaches, especially those incorporating preperitoneal mesh placement, offer potential benefits by avoiding close proximity to nerves in the inguinal canal and reducing pain.      Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result Our search produced 11 results. After looking at the titles and summaries, we found several  papers that fit our criteria. At first, we excluded few articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included prospective randomized three-arm study with intention to treat analysis and various retrospective studies. Conclusion: The study recommends the open preperitoneal approach for inguinal hernia repair, citing lower recurrence rates and reduced midline laparotomy instances, especially beneficial in cases involving intestinal resection. Additionally, a comparison between Transrectus Sheath Preperitoneal (TREPP) and Transinguinal Preperitoneal (TIPP) approaches reveals comparable chronic pain rates, with TIPP favored for learning curve-associated recurrences and superior short-term pain outcomes in TREPP, highlighting the importance of individualized surgical choices.